2016
DOI: 10.4085/1062-6050-51.9.10
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Injuries During Military Static-Line Airborne Operations: A Systematic Review and Meta-Analysis

Abstract: Objective: To identify and analyze articles in which the authors examined risk factors for soldiers during military staticline airborne operations.Data Sources: We searched for articles in PubMed, the Defense Technical Information Center, reference lists, and other sources using the key words airborne, parachuting, parachutes, paratrooper, injuries, wounds, trauma, and musculoskeletal.Study Selection: The search identified 17 684 potential studies. Studies were included if they were written in English, involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 54 publications
0
25
0
4
Order By: Relevance
“…1-3). Table 2 Distribution of trauma site, injury site, diagnosis and treatment method applied according to ISS n (%) (5,9) Descriptive statistics are given as numbers (%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1-3). Table 2 Distribution of trauma site, injury site, diagnosis and treatment method applied according to ISS n (%) (5,9) Descriptive statistics are given as numbers (%).…”
Section: Resultsmentioning
confidence: 99%
“…In the study where A.Westman et al examined the deadly events due to free fall between 1981-2006, Building-Antenna-Span-Earth jumping(BASE), due to reasons related to human, environment and equipment (parachute-related problems, due to reverse airflow, loss of vision due to weather, or acrobatic movements), deaths have been reported (6). Similar factors have been reported to be effective in injuries, as well as high rates of injury during nighttime jumps (9). In the literature studies, the wrong landing technique was mentioned as the most common cause of injury (4,19).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The half-squat parachute landing (HSPL) posture has been adopted by Chinese paratroops [2,3]. When compared with the sideways roll parachute landing fall, the HSPL method may reduce the probability of asynchronous landings on either the left or right foot [4]. In this maneuver, the upper body is in a neutral stance, and the lower extremities are in a half-squat position, with the legs slightly bent and extended forward.…”
Section: Introductionmentioning
confidence: 99%
“…The protective performance of the ankle brace depends on not only its material, structure, and application method, but also its protective effect on the biomechanical mechanism of the ankle injury. Knapik et al recorded 33,461 instances of parachute jumping with ankle braces and 69,323 instances of parachute jumping without ankle braces, and the results show the injury rate of the latter was 1.83-2.0 times higher than that of the former [4]. Wu et al found that the greater the average angular velocity of inversion and dorsiflexion, the more likely it would cause ankle joint instability on the coronal and sagittal planes.…”
Section: Introductionmentioning
confidence: 99%